Ub̈er die Rekonstruktion der Handlung "Einkaufen im Bioladen" - ein Beispiel fur̈ qualitative Sozialforschung nach der "Grounded Theory" - Simone Helmle (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2005)
– This article presents a study about the symbolic significance of shopping in the organic store. The data are based on autobiographic reports and analyzed using grounded theory. The result is a concept with finding of identity and well-being as the main categories. According to these categories, hypotheses about the structures of personal values were proposed. Such structures are the perception of an alternative lifestyle as something normal, sympathetic ideas towards farm production and ideas about self-sufficiency. A strong point of the analysis is the abundance of empirical material, but the small number of cases and the subjects strong philosophical nature are restrictive.
Keywords: 330; Bio-Lebensmittel; Konsumentenverhalten; Qualitative Methode